Essential infantile esotropia - D.R. Mamulat; I.L. Plisov; N.G. Antsiferova; M.A. Sharokhin; K.A. Belousova; G.V. Gladysheva; V.B. Pushchina (Офтальмохирургия)
Relevance. Essential infantile esotropia (EIE) is the most common type of childhood strabismus. The incidence of EIE varies on average from 0.1 to 1.0% in the general population of children, which is significant for timely diagnosis and provision of appropriate assistance to this category of patients. The exact etiology of infantile essential esotropia remains unknown, but historically a number of conflicting theories have been proposed. Purpose. To summarize the accumulated experience in the field of studying EIE to determine the optimal path to achieving the main goal of treatment – achieving orthoposition with the subsequent formation of binocular vision in this category of patients. Material and methods. To complete the review, a search of literature sources was carried out in the PubMed and Scopus abstract databases for the period up to 2022 inclusive. A total of 32 articles relevant to the review topic were selected and analyzed. Results. Having analyzed the literature data, we can conclude that today there is no unified classification of infant essential esotropia, but a certain symptom complex of clinical manifestations has been identified that are pathognomonic for this type of strabismus. Usually, EIE manifests in the first 6 months of life, appears a large horizontal esodeviation, may be accompanied by latent nystagmus, compensatory head rotation, and cross-fixation syndrome. This type of strabismus occurs in infants with normal age-related refraction and normal neurological status. The clinical approach to tactics and methods of treatment of infantile esotropia varies widely in the strabismus world. There are conflicting opinions regarding the following issues: the optimal timing for the operation, the most effective type of operation, and what determines the favorable outcome of the treatment of essential congenital esotropia. Conclusion. Many aspects of EIE remain controversial and poorly defined. To optimally realize the main goal of EIE treatment – achieving orthoposition with the subsequent formation of binocular vision – is a feasible task, which will soon find a solution.